Respuestas

2012-06-19T03:05:10+02:00

a : -15=-3 +2x-6

a: -15 +9=2x                 X=-3


a) -6=2x



b)-3x-2x-1=-1

-5x=o


X=0


c)8-(-7x-6-(-2))

  8-(-7x-6 +2)

8 +7x +6-2

7x +12                

                                          

                                            

2012-06-19T04:22:37+02:00

Aver nose que es lo que queres saber, pero si es resultado te lo pongo:

A- Resultado=   -17

-15/-3= -5

2x-6= -12

-5 + -12

B- Resultado: -6

-3x-2= 6

-1/-1=-1

6x-1= -6

C- 52

-7x-6: 42

42 -(-2)= 44 

8-44=52